2020
DOI: 10.1101/2020.04.10.20058222
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding Economic and Health Factors Impacting the Spread of COVID-19 Disease

Abstract: The rapid spread of the Coronavirus 2019 disease had drastically impacted life all over the world. While some economies are actively recovering from this pestilence, others are experiencing fast and consistent disease spread, compelling governments to impose social distancing measures that have put a halt on routines, especially in densely-populated areas.Aiming at bringing more light on key economic and public health factors affecting the disease spread, this initial study utilizes a quantitative statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Another work by Farseev et al . [11], covers similar economic and health factors for COVID-19 spread. The study unveils significant relationships between COVID-19 and other national statistics.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Another work by Farseev et al . [11], covers similar economic and health factors for COVID-19 spread. The study unveils significant relationships between COVID-19 and other national statistics.…”
Section: Related Workmentioning
confidence: 99%
“…Another work by Farseev et al . [11] is the study of economic and health factors impacting the COVID-19 disease spread resulting in the formation of four country clusters. Siddiqui et al .…”
Section: Introductionmentioning
confidence: 99%
“…Initial reports suggested a negative correlation between BCG vaccination coverage and COVID mortality and infection rates [6], [7], however, these observations were negated subsequently due to significant bias from many confounders such as demographics, testing rates and the stage of the pandemic in each country [8], [9], [10], [11]. Several other studies have shown inconsistent or weak correlations and have not sufficiently addressed interactions or confounding [5], [12], [13], [14]. Therefore, an integrated approach to decipher the network of determinants of COVID-19 burden is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the different factors and intervention measures on the spread of COVID-19 vary. Identifying key factors that most contribute to the rapid spread of COVID-19, and accurately estimating the potential impact of different non-pharmaceutical measures for containing COVID-19 are crucial for planning the most effective interventions to curb the spread of Covid-19 (Farseev et al 2020).…”
Section: Introductionmentioning
confidence: 99%